MIXED SCALING APPROACH TO ESTABLISH BIOEQUIVALENCE OF LANSOPRAZOLE DELAYED RELEASE CAPSULE IN FASTING SPRINKLE WITH APPLE SAUCE STUDY IN HEALTHY SUBJECTS - V, Chandrakala; Sanki, Utpal Kumar; Mandal, Badal Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the present study was to establish bioequivalence of highly variable generic lansoprazole (LSP) delayed release (DR) capsule, exploring minimal number of healthy volunteers by mixed scaling approach as oppose to average bioequivalence approach. Methods: This was an open-labeled, three-treatment, three-periods, three-sequences, single-dose, partial replicate crossover trial conducted in 36 + 4 (stand by) healthy adult human subject in Indian origin. Results: Non-parametric Wilcoxon sign rank test at 95% confidence interval failed to conclude significance difference in T and t1/2 between the formulations. The intra subject standard deviation of the reference formulation was 0.340 for C , 0.249 for area under curve up to last measurable time point (AUCT) and 0.244 for area under curve up to infinity time (AUCI) parameters. The reference scaling as proposed by Haider et al., 2008, was applied for C max, max and constant scaling was applied for AUCT and AUCI metrics. No significance difference between two formulations were observed when data were analyzed by Analysis of Variance (p<0.05). Westlake 90% confidence limit, as well as two one-sided t-test as proposed by Schuriman and the Anderson-Hauck power analysis all fell under the predefine bioequivalence criteria for mixed scaling. Conclusion: The generic LSP DR capsules were found to bioequivalent with reference drug under fasting study with apple sauce with respect to rate and extent of absorption. The mixed scaling statistical analysis approach used to establish bioequivalence with a minimum number of subjects was found reliable and utilize 40 subjects as opposed to 110 subjects need to establish bioequivalence in traditional average bioequivalence approach. Keywords: Mixed scaling, Techniques, Non-parametric, Bioequivalence, Delayed release.